Do Company Builders Create Jobs? Examining the Rise of Incubation Finance in Germany - Christoph Scheuplein; Julian Kahl (Institut Arbeit und Technik (IAT), 2017)
Over the past decade, new types of business incubation have been developed. One particularly prominent example is company builders, which use their own resources to build up companies, establishing numerous companies in a series. In doing so, this investor type facilitates internal and external business ideas. It offers a new organizational solution that combines both the innovative capacity of founders and the financial re-sources of a large company with the desire for long-term employment and corporate affiliation. This article examines the economic impact of company builders in Germany compared with other venture capital (VC) investor types on the basis of employment trends in the portfolio companies from 2011 to 2015. It is shown that company builders promote more dynamic employment growth than do other types of investors. This finding suggests that this type of investor is particularly well positioned to take advantage of the institutional deficiency in the German VC market. The results are also discussed in the context of the growth of the Berlin-based VC and start-up ecosystem.
Keywords: G24; M13; L22; R12; 330; venture capital; company builder; incubation; employment; Germany